Penerapan Design Thinking Pada Perancangan Desain UI/UX Sistem Tracking Kesehatan - Budi Santoso; Indra Sumantiawan, Dody (LPPM Universitas Mulia, 2025)
The utilization of digital technology in the healthcare sector is crucial, including within educational environments. At SMK Bagimu Negeriku, which implements a boarding school model, the recording of students' health information is still conducted manually, posing risks of data loss or improper documentation. Therefore, a digital system is needed to simplify the recording and monitoring of students' health information. By designing the UI/UX for a health tracking system, it is expected to create an efficient solution and provide the best experience for all users, including dormitory supervisors and school administrators, in efforts to maintain students’ health both preventively and curatively. The applied method is the Design Thinking approach, encompassing the stages of Empathize, Define, Ideate, Prototype, and Testing. Each stage is conducted to ensure that the design meets the users' needs and preferences. The resulting prototype was evaluated through usability testing using the System Usability Scale (SUS). The evaluation results showed a SUS score of 85 out of 100, indicating a high level of usability and user satisfaction.